Ta’līmu al Mahārati al Kitābati fī Qismi al Lughati al Arabiyyati bi Istikhdāmi Tarkībi al Maḥfūẓāti - Yul, Widiya; D.S., Muhammad Ridha; Ghozi, Mohamad (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
The writer produces it by generating ideas, formulating and organizing them, and then putting them in the final form on paper, and it is a type of language skill that must be achieved in teaching Arabic. Given the importance and function of language as a communication tool, learning to write the Arabic language becomes very important because it is used in indirect communication that requires special attention by teachers or interested parties.Writing skills that do not fit into practice become one of the factors that lack students' writing skill but are not fully implemented. Arranging idea, opinion and experience in a series of organized, systematic and logical written languages is not an easy task but a job that requires continuous practice, through teaching writing skill using archival structure is one of the methods used to achieve the set goals.